The Imagined And The Concrete: What is an Artifact? - Susan M. Hagan (Artifact, 2007)
Abstract A few years ago, in conversation with a friend in engineering, I mentioned that I had been collecting and analyzing artifacts – conference covers, magazine layouts, art history texts – anything that might help me understand how words, typography, and images collaborate on the page to make messages that could not be produced by text or image alone. But our discussion did not get past my use of the term artifact. My colleague simply could not wrap his mind around the idea that an artifact’s third dimension could be so narrow, its material so contemporary, and its value so seemingly insignificant. He cautioned me against the use of that term. I conceded the point. Were I to encounter that friend today, I would not only apply the term artifact to my data, I would take that claim further.